Vliyanie pogodnykh uslovij na effektivnost i stoimost protsessa podgotovki v parusnom sporte - Akimenko, V. I.; Georgyan, G. A. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
About the influence of the weather in the sport of sailing and what has to be taken in mind in training planning under the weather aspect.